Optimal Stroke Prevention in the Geriatric Patient with Atrial Fibrillation: Position Paper of an Interdisciplinary Expert Panel - Bahrmann, P.; Wehling, M.; Ropers, D.; Flohr, J.; Leischker, A.; Röther, J. (Drug Research, 2015)
The present position paper summarises the outcomes of an expert panel discussion held by hospital-based and office-based physicians with ample experience in the treatment of geriatric patients. The optimal approach to stroke prevention in geriatric patients with atrial fibrillation (AF) has not been adequately clarified. Despite their high risk of stroke and clear indication for anticoagulation according to established risk scores, in practice geriatric AF patients often are withheld treatment because of comorbidities and comedications, concerns about low treatment adherence or fear of bleeding events, in particular due to falls. The panel agreed that geriatric patients should receive oral anticoagulation as a rule, unless a comprehensive neurological and geriatric assessment (including clinical examination, gait tests and validated instruments such as Modified Rankin Scale, Mini-mental state examination or Timed Test of Money Counting) provides sound reasons for refraining from treatment. All patients with a history of falls should be thoroughly evaluated for further evaluation of the causes. Patients with CHADS2 score ≥ 2 should receive anticoagulation even if at high risk for falls. The novel oral anticoagulants (NOAC) facilitate management in the geriatric population with AF (no INR monitoring needed, easier bridging during interventions) and have, based on available data, an improved benefit-risk ratio compared to vitamin K antagonists. Drugs with predominantly non-renal elimination are safer in geriatric patients and should be preferred.
Keywords: older patients; geriatrics; assessment; adherence; atrial fibrillation; stroke; prevention; interdisciplinary management; atrial fibrillation; anticoagulation; novel anticoagulants